Friends or Followers? The Relations between German Soccer Clubs and Their Fans on Twitter - Weller, Katrin; Bruns, Axel (AoIR Selected Papers of Internet Research, 2013)
This paper shows how soccer clubs from Germany’s first division have started to use Twitter. Analysis is based on tweets from and to club accounts as well as on follower numbers, and specific clubs are selected for case studies. This approach reveals that Twitter mirrors the conflicts between professional sports and traditional fandom.